Hydrogenases from sulphate reducing bacteria and their role in the bioremediation of textile effluent - Mutambanengwe, Cecil Clifford Zvandada (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2007)
The continuing industrial development has led to a corresponding increase in the amount of waste water generation leading to a consequential decline in levels and quality of the natural water in the ecosystem. Textile industries consume over 7 x 10[superscript 5] tons of dyes annually and use up to 1 litre of water per kg of dye processed and are third largest polluters in the world, the problem being aggravated by the inefficiencies of the dye houses. An abundance of physio-chemical methods are in use world wide, however, there is increasing concern as to their impact in effectively treating textile effluents as they introduce secondary pollutants during the 'remediation' process which are quite costly to run, maintain and clean up. Research on biological treatment has offered simple and cost effective ways of bioremediating textile effluents. While aerobic treatment of textile dyes and their effluents has been reported, its major draw back is commercial up-scaling and as such anaerobic systems have been investigated and shown to degrade azo dyes, which form the bulk of the dyes used world wide. However, the mechanisms involved in the bioremediation of these dyes are poorly understood. The aims of this study were to identify and investigate the role of enzymes produced by sulphate reducing bacteria (SRB) in bioremediating textile dye and their effluents. Sulphate reducing bacteria were used in this study because they are tolerant to harsh environmental conditions and inhibit the proliferance of pathogenic micro-organisms. The appearance of clear zones in agar plates containing azo dye concentrations ranging from 10 "“ 100 mgl[superscript -1] showed the ability of SRB to decolourize dyes under anaerobic conditions. Assays of enzymes previously reported to decolourise azo dyes were not successful, but led to the identification of hydrogenase enzyme being produced by SRB. The enzyme was found to be localised in the membrane and cytoplasm. A surface response method was used to optimize the extraction of the enzyme from the bacterial cells resulting in approximately 3 fold increase in hydrogenase activity. Maximum hydrogenase activity was found to occur after six days in the absence of dyes but was found to occur after one day in the presence of azo dyes. A decline in hydrogenase activity thereafter, suggested inhibition of enzymatic activity by the putative aromatic amines produced after azo cleavage. Purification of the hydrogenase by freeze drying, poly ethylene glycol, and Sephacryl "“ 200 size exclusion- ion exchange chromatography revealed the enzyme to have a molecular weight of 38.5 kDa when analyzed by a 12 % SDS-PAGE. Characterisation of the enzyme revealed optimal activity at a pH of 7.5 and temperature of 40 Â°C while it exhibited a poor thermal stability with a half-life of 32 minutes. The kinetic parameters V[subscript max] and K[subscript m] were 21.18 U ml[superscript -1} and 4.57 mM respectively. Application of the cell free extract on commercial dyes was not successful, and only whole SRB cells resulted in decolourisation of the dyes. Consequently trials on the industrial dyes and effluents were carried out with whole cells. Decolourisation rates of up to 96 % were achieved for the commercial dyes and up to 93 % for the industrial dyes over a period of 10 days.
Keywords: Bioremediation; Dyes and dyeing -- Waste disposal; Sulfur bacteria; Hydragenase; Factory and trade waste -- Purification; Textile waste